Interpersonal Communication between Teachers and Students in Forming the Character of High School Students When the New Era Covid-19 is Normal in Tangerang District (Case Study of SMAN 30 Tangerang Regency) - Qodriyah, Laelatul; Rakhma, Dinda (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
This article examines the Interpersonal Communication of Teachers and Students in Shaping the Character of School Students in the New Normal Era, because at the time of the new normal which means a new normal life during the covid-19 pandemic, the teaching and learning process is carried out indirectly, of course by utilizing online media such as Whatsapp. , google forms, and zoom meeting. The implementation of character education, which is usually taught through habits in schools, must be changed online. In the world of education, students really need character to shape their personality. This research includes descriptive qualitative research. The subjects in this study were teachers and guardians of students at SMA Negeri 30 Tangerang Regency. The data collection technique used is the observation of the implementation of character education. Observational data obtained were then reported descriptively. The results obtained from observations where the implementation of character education in the new normal era is carried out online. Forming student character during the current pandemic is certainly not easy for teachers, teachers must really work hard for how students are interested in learning to use media such as cellphones by sending a lot of learning material in the form of videos, communication is very limited, teachers cannot monitor directly students, then the role of parents is very important to assist teachers in online learning methods during a pandemic like this.